Maternal stress in the fetal anomaly screening process: A prospective cohort study - Batool Zeidabadi; Abedin Iranpour; Fatemeh Alavi-Arjas; Mohammad Reza Baneshi; Salman Shamsadini Moghadam; Mohammd Moqaddasi Amiri; Mahdiye Taheri (Golestan University of Medical Sciences, 2024)
Background: Fetal health and pregnancy outcomes are significant contributors to increased prenatal stress. The effect of fetal anomaly screening on a mother's stress is controversial. The present study aimed to explore maternal stress throughout a multi-stage anomaly screening program among healthy pregnant women. Methods: This prospective cohort study was conducted at the public health centers of Sirjan, Iran from March 2022 to January 2023 using the convenience sampling process. The population included 228 healthy pregnant women. Data were collected using a researcher-made checklist for demographic and obstetrics characteristics. Cohen's Perceived Stress Scale (PSS) was utilized to measure maternal stress at three distinct intervals, including before (weeks 6-10 of pregnancy), during (weeks 11-14 of pregnancy), and after fetal anomaly screening tests (weeks 15-20 of pregnancy). Friedman test was used for measuring the association between maternal stress and fetal abnormality test results. Data were analyzed with Statistical Package for the Social Sciences (SPSS) software version 26 at a significance level of 0.05. Results: The mothers with higher educational levels (p =0.05, β=1.74), and having a live child experienced lower levels of initial stress (p =0.016, β=2.27). Throughout the time, receiving a normal nuchal translucency (NT) result was associated with a significant decrease in perceived mother's stress (p <0.0001), and abnormal NT ultrasound results (reported in 3.8% of women) led to a rise in the downslope of stress in the third measurement; however, it was not significant. Conclusion: The present study revealed that maternal stress decreased over time following normal results of fetal anomaly screening. Three factors were associated with lower maternal stress, including university education, having at least a living child, and a normal ultrasound result. Moreover, women at first pregnancy and/or with an abnormal ultrasound result experienced high-stress levels. The findings may be useful in guiding the formulation of health policies and the distribution of resources.